2013
DOI: 10.1007/s00284-013-0489-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Pleurotus pulmonarius Revealed by RAPD, ISSR, and SRAP Fingerprinting

Abstract: Pleurotus pulmonarius is one of the most widely cultivated and popular edible fungi in the genus Pleurotus. Three molecular markers were used to analyze the genetic diversity of 15 Chinese P. pulmonarius cultivars. In total, 21 random amplified polymorphic DNA (RAPD), 20 inter-simple sequence repeat (ISSR), and 20 sequence-related amplified polymorphism (SRAP) primers or primer pairs were selected for generating data based on their clear banding profiles produced. With the use of these RAPD, ISSR, and SRAP pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
5
11
0
Order By: Relevance
“…(BPSM10 and BPSM34) has been closely clustered together. This finding was similarly reported by Yin et al [20] and Ro et al[72] who reported that phenotypic characteristics of fruiting bodies of. P .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(BPSM10 and BPSM34) has been closely clustered together. This finding was similarly reported by Yin et al [20] and Ro et al[72] who reported that phenotypic characteristics of fruiting bodies of. P .…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we selected two DNA based markers like randomly amplified polymorphic DNA (RAPD), and inter-simple sequence repeats (ISSR) to understand the genetic diversity among the wild mushrooms as these marker systems have been routinely employed to assess genetic diversity [19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…Cluster I were further separated in to two sub cluster (A and B) with 67.5% diversity. The result is confirmative with finding of Yin et al, (2013) who investigated that the molecular markers were used to analyze the genetic diversity of 15 Chinese P. pulmonarius cultivars. In total, 21 RAPD primers selected for generating data based on their clear banding profiles produced.…”
Section: Resultssupporting
confidence: 64%
“…The protocol is simple, efficient, and has a high production rate. It has been used successfully in genetic diversity analysis and construction of genetic maps of many plant species [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%